Gamma knife radiosurgery for local recurrence of glioblastoma - Guseynova, Khumar; Liscak, Roman; Simonova, Gabriela; Novotny, Josef (Neuro endocrinology letters, 2018)
OBJECTIVE: Local recurrence of glioblastoma is observed in most patients after standard oncologic treatment (surgery, chemotherapy and radiotherapy). Stereotactic radiosurgery with the Leksell Gamma Knife (SRS with LGK) was used to treat recurrent tumors in selected cases, and retrospective analysis of treatment outcome was performed. METHODS: Altogether 126 patients were treated for glioblastoma at our center from 1992-2014. Sixty-nine patients (55%) were male and 57 (45%) female, with a median age of 56 years (range 17-80 years). Prior to LGK radiosurgery, 123 (98%) underwent surgery, 126 (100%) radiotherapy and 116 (92%) chemotherapy. The median Karnofsky score before LGK radiosurgery was 90% (range 50-100), and the median time from GBM diagnosis to LGK radiosurgery was 12 months (range 1-96 months). The median tumor volume was 3.75 cm3 (range 0.04-37.10 cm3). LGK radiosurgery was performed in a single fraction with a median minimal tumor dose of 12 Gy (range 10-25 Gy) on a median 50% (range 40-86%) isodose line. Two and more LGK radiosurgeries were performed in 19 (15%) cases, a median interval of 9.6 months (range 2-45 months) from the initial LGK radiosurgery. The median prescribed dose in these patients was 12.6 Gy (range 10-15 Gy), and the median volume 5.8 cm3 (range 0.1-13.7 cm3). RESULTS: The median survival from GBM diagnosis was 20 months (range 6-237 months). The median survival after LGK radiosurgery was 7 months (range 1-223 months). The one year survival after LGK radiosurgery was 27%, 2 years 8%, and more than 3 years 4%. Tumor regression on MR images was observed in 17% of patients at a median interval of 7 months. The median interval to tumor progression on MR images after LGK treatment was 8.5 months. No treatment-related radionecrosis with expansive behaviour was detected after radiosurgery. CONCLUSION: We show that LGK radiosurgery is a safe palliative treatment modality in patients with recurrent GBM.
Keywords: nádory mozku; Humans; lidé středního věku; Brain Neoplasms; Palliative Care; Female; Aged; mladý dospělý; dospělí; výsledek terapie; senioři; lidé; glioblastom; radiochirurgie; Adult; Radiosurgery; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Adolescent; Treatment Outcome; paliativní péče; Aged, 80 and over; Young Adult; Glioblastoma; senioři nad 80 let; retrospektivní studie; lokální recidiva nádoru; míra přežití; mužské pohlaví; Neoplasm Recurrence, Local; mladiství; Survival Rate